Penguatan Kompetensi Pedagogik Pembelajaran Aktif untuk Guru MTs dan Pondok Pesantren Kecamatan Kunto Darussalam Kabupaten Rokan Hulu - Erni, Sukma; Roza, Ellya; Miski, Cut Raudhatul; Pahlepi, Anisa (Jurnal SOLMA, 2025)
Background: On Post Covid 19, many schools experienced a decline, especially in the learning process. Students who have been at home for a long time, accustomed to gadgets, often seem to lose concentration in learning and focus more often on Google. One effort to restore students' focus on learning in class is of course by building meaningful learning. This community service activity aims to provide pedagogical reinforcement of active learning for teachers so that the learning situation becomes meaningful. Method: It is carried out by combining the ABCD method and Class Action to find out the needs of teachers and ensure that teachers have mastered and can practice them. The results of the mapping obtained are that teachers need training related to learning. Based on the results of the mapping, it was agreed to carry out active learning training, practice in training and post-training practice. Result: The results obtained are that teachers can practice several strategies that spark active learning. Teachers also feel satisfied and happy. The seriousness of the teachers is also evident from the learning practices uploaded to YouTube and Facebook so that they can share good practices of the teachers' actions. Conclusions: This activity is that pedagogical strengthening training is needed for teachers, especially in remote areas.